Morphometrics and Meristics of Senangin (Eleutheronema Tetradactylum) Results of Gillnet Catch in Mendahara Ilir of East Tanjung Jabung District - Haryani, Nova; Lisna, Lisna; Magwa, Rizky Janatul; Nelwida, Nelwida; Gelis, Ester Restiana Endang; Farizal, Farizal (Journal of Fish Health, 2025)
Mendahara Ilir is an area located on the coast with the majority of the community working as fishermen. Fishermen in this area catch fish using Gillnet fishing gear. Overfishing is a form of excessive fishing, the fish population is decreasing over time so that it can cause extinction and will cause degradation of fish resources leading to the extinction of the Senangin species. The purpose of this study was to determine the morphometric and meristic measurements of Senangin (Eleutheronema tetradactylum) in the waters of Mendahara Ilir which can be used as a consideration in making fisheries resource management policies. The method used in this study was the survey method. Data collection was carried out on 30 Senangin samples. Morphometric measurements used 11 characters and meristic calculations used 7 characters. The results of this study showed that the longest Senangin was 65.8 cm and the shortest was 19.0 cm. The average length of the Senangin obtained was 34.7 cm. The determination coefficient R2 of senangin from morphometric characters to total length (TL) ranges from 0.94 to 0.99 where the value shows a very close relationship. The correlation results are influenced by food availability. Meristics of senangin are D.II; D17-19, A.II: A15-70, P.II: 10-76, C.II: 31-182, scales on the tail stem with a total of 136 and a minimum number of 40, lateral line scales with a total of 170 and a minimum number of 62. The conclusion is that Senangin in the Mendahara Ilir waters are still well maintained habitat in Mendahara Ilir.